2017
DOI: 10.1002/elsc.201600228
|View full text |Cite
|
Sign up to set email alerts
|

Carotene production from waste cooking oil by Blakeslea trispora in a bubble column reactor: The role of oxidative stress

Abstract: The oxidative stress induced by hydroperoxides and reactive oxygen species (ROS) during carotene production from waste cooking oil (WCO) and corn steep liquor (CSL) by the fungus Blakeslea trispora in a bubble column reactor was investigated. The specific activities of the intracellular enzymes superoxide dismutase (SOD) and catalase (CAT) as well as the micromorphology of the fungus were measured in order to study the response of the fungus to oxidative stress. The changes of the morphology of microorganism l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The highest yield (2 gÁL À1 ) was obtained using WCO as sole carbon source supplemented with corn steep liquor and butylated hydroxytoluene, and in this condition the carotenes produced consisted of b-carotene (74.2 %), c-carotene (23.2 %) and lycopene (2.6 %). Upscaling the process to a 1.4-L bubble column reactor did not favored the production of carotenes and lower amount was attained comparatively to flask experiments (Nanou, Roukas, Papadakis, & Kotzekidou, 2017).…”
Section: Other Compoundsmentioning
confidence: 74%
“…The highest yield (2 gÁL À1 ) was obtained using WCO as sole carbon source supplemented with corn steep liquor and butylated hydroxytoluene, and in this condition the carotenes produced consisted of b-carotene (74.2 %), c-carotene (23.2 %) and lycopene (2.6 %). Upscaling the process to a 1.4-L bubble column reactor did not favored the production of carotenes and lower amount was attained comparatively to flask experiments (Nanou, Roukas, Papadakis, & Kotzekidou, 2017).…”
Section: Other Compoundsmentioning
confidence: 74%
“…Therefore, carotenoids do not play a major physiological role in fungal cells, but they may have beneficial effects under specific conditions. Several studies showed an increase in carotenoid concentration under stress [45,57]. The potential photoprotective pigment torulene [9,58] showed low concentrations in K. petricola A95, which would imply a less important role in K. petricola A95, but an inducible production under a stress situation out of the more stable dehydrolycopene seems possible.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the stable carotenoid concentrations in K. petricola A95 would be that the mechanism of carotenoid action is more likely to consist of shielding sensitive molecules or organelles than of neutralization of harmful oxidants [51]. under stress [43,52]. The potential photoprotective pigment torulene [6,53] showed low concentrations in K.…”
Section: Discussionmentioning
confidence: 99%